Development of faculty navigation and class listings mobile applications: class route / Muhamad Akif Naim Zakaria and Muhammad Irfan Md Zulnorrain - Zakaria, Muhamad Akif Naim; Md Zulnorrain, Muhammad Irfan (Universiti Teknologi MARA (UiTM), 2024)
This navigation application development project was created with the goal of identifying and studying the latest technology of geospatial navigation applications in development, as well as developing an area level application to find the local location (class) of directions around the UiTM Seri Iskandar area. According to current technology, there are now many connections between the outside world, which now has Google Earth, Waze, and so on that can solve the problem of going to a location, even now with the creation of this application, it is generally directly studied in relation to navigation that can provide continuity in geospatial technology itself and bring to life and directly be able to introduce advanced technology.